Trypanosomiasis in N'Dama cattle in Zaire and its effects on their health and production - Mulungo, M.; D'Ieteren, G.D.M.; Feron, A.; Itty, P.; Maehl, H.M.; Nagda, S.M.; Paling, R.W.; Rarieya, J.M.; Thorpe, W.R.; Trail, J.C.M. (OAU/STRC, 1988)
Reports the prevalence, species and intensity of trypanosome infections over a 3 year period for N'Dama cattle managed on Mushie Ranch, Zaire. Presents the effects of the trypanosome infections on blood packed cell volume reproductive performance and liveweights.